Determinants of Firm Value: Evidence from Carbon Emission Disclosure, Green Innovation, and Cash Holding - Mutiara Ilmiana Nur Isfani; Ahmad Zakia Garda Pratama (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to obtain empirical evidence on the influence of carbon Emission Disclosure, Green Innovation, and Cash Holding on Firm Value. Design/methodology/approach – This study uses quantitative research. The sample in this study consist of 40 companies in the transportation and logistics, and infrastructure sectors listed on Indonesian Stock Exchange from 2021-2024. The analysis technique used to the hypothesis is multiple regression analysis using Eviews 9 software. Findings – The results of this study found carbon emission disclosure had a negative and statictically insignificant effect on firm value, while green innovation had a negative and statistically significant effect on firm value, and cash holding had a positive and statistically significant effect on firm value. Research limitations/implications – This study discusses firm value and other such as carbon emission disclosure, green innovation, and cash holding focusing on transportation and logistics, and infrastructure sectros.